Self-Quoting in Moliere’s Comedies: Original Text and Translations - Svetlana Yu. Pavlova (Studia Litterarum)
The article is devoted to autoreferentiality in Molière’s comedies, namely, his selfquoting. It is found in plays of a theoretical nature — Critique of the School for Wives (1663) and The Versailles Impromptu (1663). These comedies were the playwright’s response to the so-called Dispute over the School for Wives (1662). Cases of selfquoting are considered in the context of the aesthetic and ethical claims that were put forward by Moliere’s opponents, and also his idea of laughter, the comic potential of images, and the peculiarities of stage language. The article argues that self-citations are metatheatrical since they reflect Molière’s reflection on the tasks of comedy. The analysis of self-quoting is carried out taking into account the most authoritative translations of the three plays into Russian (they were performed by eight translators in total), included in the Complete Works of Molière, published in the 20th century. The research shows that in Russian translations, the author’s self-quotations are not always preserved; the translations also contain semantic inaccuracies due to the differences in cultural context. It inevitably influences the understanding of Molière’s plays. The largest number of discrepancies is contained in pre-revolutionary publications. From the point of view of recognizability of self-quoting, the translations of the Soviet period seem to be more successful. The study shows the importance of self-quoting in Molière’s plays and testifies to the need for new Complete Works in which all the elements of autoreferentiality will be made clear to the Russian reader and commented on.